Case note on CJEU 14 November 2024, ECLI:EUC:2024:952, C-394/22 (Oilchart) - Veder, Michael (European Insolvency and Restructuring Journal, 2025)
In Skarb v Riel (C‑47/18), the Court of Justice of the European Union held that actions aimed at verifying the existence of a creditor’s claim in insolvency proceedings are excluded from Brussels I-bis and fall within the scope of the European Insolvency Regulation, so that jurisdiction lies exclusively with the courts of the Member State where the proceedings were opened. By contrast, in Oilchart (C‑394/22), the CJEU emphasized that the legal basis of a claim is decisive, ruling that a contractual claim does not derive directly from insolvency proceedings even if it is also submitted in such proceedings. This case note examines the divergent approaches of the CJEU – contrasting its decisions with an earlier stance of the Dutch Supreme Court regarding forum selection clauses in bankruptcy – and considers the implications for the potential of conflicting decisions on claim verification.